2021
DOI: 10.3390/batteries7020021
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Diffusion Coefficients of Lithium in Solid Electrolyte LiPON

Abstract: A structural model of LiPON solid electrolyte, containing elements that simulate drift conductivity, diffusion conductivity, and leakage current was proposed. The dependence of the impedance of the structural model on frequency was calculated, and the parameters of the model at which the theoretical curve best approximates the experimental Nyquist diagrams were determined. Based on these data, the ion diffusion coefficient and conductivity of LiPON were calculated, which are D1 = 1.5 × 10−11 cm2/s and σ = 1.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
(15 reference statements)
0
6
0
1
Order By: Relevance
“…We can re‐write Equation as: ctbadbreak=1x(M01c0cfalse(1goodbreak−cfalse)cxtrueμ˜c)goodbreak=1x(Dcx)\[\frac{{\partial c}}{{\partial t}} = - \frac{1}{{\partial x}}\left( {{M_{01}}{c_0}c(1 - c)\frac{{\partial c}}{{\partial x}}\frac{{\partial \tilde{\mu }}}{{\partial c}}} \right) = - \frac{1}{{\partial x}}\left( {D\frac{{\partial c}}{{\partial x}}} \right)\] Where D, the diffusion coefficient, has been defined as: Dbadbreak=M01c0false(1goodbreak−cfalse)trueμ˜cgoodbreak=M01c0false(1cfalse)q0ϕOCVc\[D = {M_{01}}{c_0}(1 - c)\frac{{\partial \tilde{\mu }}}{{\partial c}} = - \frac{{{M_{01}}{c_0}(1 - c)}}{{{q_0}}}\frac{{\partial {\phi _{{\rm{OCV}}}}}}{{\partial c}}\] The model depends now on the two parameters ϕ OCV ( c ) and M 01 , and their dependence with respect to the intercalation fraction c ; both being experimentally measured by means of the galvanostatic‐intermittent‐titration technique(GITT). [ 46–50 ] In the present work, GITT is performed on a 10 µm LCO device at 25°C. The temperature does not impact the LCO diffusion, due to the high activation energy (Figure , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We can re‐write Equation as: ctbadbreak=1x(M01c0cfalse(1goodbreak−cfalse)cxtrueμ˜c)goodbreak=1x(Dcx)\[\frac{{\partial c}}{{\partial t}} = - \frac{1}{{\partial x}}\left( {{M_{01}}{c_0}c(1 - c)\frac{{\partial c}}{{\partial x}}\frac{{\partial \tilde{\mu }}}{{\partial c}}} \right) = - \frac{1}{{\partial x}}\left( {D\frac{{\partial c}}{{\partial x}}} \right)\] Where D, the diffusion coefficient, has been defined as: Dbadbreak=M01c0false(1goodbreak−cfalse)trueμ˜cgoodbreak=M01c0false(1cfalse)q0ϕOCVc\[D = {M_{01}}{c_0}(1 - c)\frac{{\partial \tilde{\mu }}}{{\partial c}} = - \frac{{{M_{01}}{c_0}(1 - c)}}{{{q_0}}}\frac{{\partial {\phi _{{\rm{OCV}}}}}}{{\partial c}}\] The model depends now on the two parameters ϕ OCV ( c ) and M 01 , and their dependence with respect to the intercalation fraction c ; both being experimentally measured by means of the galvanostatic‐intermittent‐titration technique(GITT). [ 46–50 ] In the present work, GITT is performed on a 10 µm LCO device at 25°C. The temperature does not impact the LCO diffusion, due to the high activation energy (Figure , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…To conclude the model development, lithium mobility in LiPON [ 50,66,67 ] and charge transfer coefficient are still missing. Electrochemical impedance spectroscopy (EIS) can provide the required information to complete the picture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 твердый электролит LiPON представлен в виде элемента постоянной фазы, что является достаточно формальным приближением. Как было показано в работе[6], его можно представить при помощи эквивалентной схемы, содержащей только идеальные структурные элементы. В настоящей работе CPE используются исключительно для удобства сопоставления с результатами других информационных источников.…”
unclassified
“…1 in the form of a constant-phase element, which is a rather formal approximation. As was demonstrated in [6], it may be substituted by an equivalent circuit with ideal structural elements only. In the present study, CPEs are used just for convenience of comparison with the results reported elsewhere.…”
mentioning
confidence: 99%